Do Profitability, Liquidity, and Capital Intensity Influence the Degree of Tax Aggressiveness? (Study on Energy Sector of the Oil and Gas Industry Listed on the Indonesian Stock Exchange) - Santy, Ruri Fila; Limarjani, Sustinah; Amalia, Wia Rizqi (Future Science, 2025)
This study seeks to investigate and assess how profitability, liquidity, and capital intensity impact tax aggressiveness. The research focuses on the energy sector within the oil and gas industry listed on the IDX from 2020 to 2023. Ten companies with a total of forty samples were included in the study. The findings reveal that both profitability and capital intensity significantly affect tax aggressiveness, suggesting that higher levels of profitability and capital intensity lead to increased tax aggressiveness. Conversely, the study found no significant relationship between liquidity and tax aggressiveness, indicating that liquidity levels do not influence corporate tax aggressiveness.